2021
DOI: 10.3390/vaccines9090990
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal ChAdOx1 Vaccine Following Two CoronaVac Shots: A Case Report

Abstract: Inactivated SARS-CoV-2 vaccines are used in many countries with uncertain immunogenicity. Intradermal ChAdOx1 has been proposed as a resource-efficient heterologous third booster shot. A 52-year-old healthy male healthcare professional had received two intramuscular CoronaVac shots on 21 April and 23 May 2021, and volunteered to take a 0.1 mL ChAdOx1 vaccine intradermally on 29 June 2021, with minimal local reactions. The declining IgG levels against spike protein from the two CoronaVac shots increased to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, participants randomized to the IM administration control arm in this study did not receive a standard dose [35] . A case report by Singhatiraj et al also showed excellent immunogenicity of an ID 20% fractional dose of AZD1222 among participants who had previously received two doses of CoronaVac [36] .…”
Section: Discussionmentioning
confidence: 93%
“…However, participants randomized to the IM administration control arm in this study did not receive a standard dose [35] . A case report by Singhatiraj et al also showed excellent immunogenicity of an ID 20% fractional dose of AZD1222 among participants who had previously received two doses of CoronaVac [36] .…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the optimized production of neutralizing secretory IgA antibodies, especially in naïve vaccine recipients, is obtained after a second-dose-induced boost, confirming the importance of the two-to-three doses SARS-CoV-2 vaccination program [ [128] , [129] , [130] ]. In addition, it is remarked that most studies reported that IgA antiviral immunity is mainly induced by mRNA-based vaccines than other vaccines, including attenuated vaccines [ 24 , 128 , [130] , [131] , [132] ], these mRNA vaccines added protective-value lies in their ability to induce neutralizing IgA.…”
Section: Introductionmentioning
confidence: 84%
“…Fractional doses 10-20% of their IM or SC dosages are generally used for ID administration ( 5 8 ). Such dose reductions could help increase vaccine supply and availability as well as reduce vaccination costs by 60-80% compared to IM regimens ( 3 , 8 , 9 ). Addressing these factors are crucial to navigating global vaccine shortages, particularly in low- and middle-income countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%